2020
DOI: 10.1002/bdr2.1651
|View full text |Cite
|
Sign up to set email alerts
|

Is preparation a good reason for prenatal genetic testing? Ethical and critical questions

Abstract: As prenatal genetic testing technologies have become both easier and more accessible, women are increasingly choosing prenatal genetic testing for a reason that is largely unexamined in the clinical literature: preparation. This reasoning, offered not only from pregnant women but frequently from testing laboratories and health care providers, reflects long‐held assumptions that prenatal genetic results—properly delivered and followed with information, clinical surveillance, and/or social supports—prepare famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Confirming the findings from other studies with different methodologies, NIPT as discussed on Reddit is seen as providing valuable means of obtaining highly sought‐after information (including early detection of sex) in a manner that is better than other tests 42,43 . Redditors not only acknowledge the value of NIPT as providing “peace of mind,” but some state how NIPT helps support their mental and organizational preparation when making difficult pregnancy decisions, including for a range of birthing outcomes 7,44,45 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Confirming the findings from other studies with different methodologies, NIPT as discussed on Reddit is seen as providing valuable means of obtaining highly sought‐after information (including early detection of sex) in a manner that is better than other tests 42,43 . Redditors not only acknowledge the value of NIPT as providing “peace of mind,” but some state how NIPT helps support their mental and organizational preparation when making difficult pregnancy decisions, including for a range of birthing outcomes 7,44,45 …”
Section: Discussionmentioning
confidence: 66%
“…42,43 Redditors not only acknowledge the value of NIPT as providing "peace of mind," but some state how NIPT helps support their mental and organizational preparation when making difficult pregnancy decisions, including for a range of birthing outcomes. 7,44,45 Redditors, however, also raise some concerns. These include anxieties that result from testing, difficulties accessing NIPT (ie, not having costs covered by insurance plans), the accuracy of NIPT results, confusion surrounding the interpretation of NIPT results, and the assistance provided by health entities regarding accessing the test and assisting with the interpretation of findings.…”
Section: Aspect Of Discussion Text Examplesmentioning
confidence: 99%
“…A common reason for women to undergo prenatal testing is to have emotional, psychological, and medical preparation if the baby has Down syndrome or other condition [91], a justification I frequently heard during my 22 years working as a genetic counselor in a busy prenatal diagnosis clinic. Interestingly, one study reported that most women who chose to continue a pregnancy with Down syndrome experienced an increase in anxiety during the pregnancy, although many women said they if they could do it over, they would still choose to undergo prenatal diagnosis again [92].…”
Section: Medical and Emotional Preparationmentioning
confidence: 99%
“…It is also unclear what emotional benefits families obtain from foreknowledge of an affected child via prenatal testing. While many women undergo testing for emotional preparation, there is no proven measurable and concrete benefit [91]. Such empirical data would be very helpful to women who are trying to decide whether to undergo prenatal testing, particularly women who would not consider abortion.…”
Section: Medical and Emotional Preparationmentioning
confidence: 99%
“…Mothers of children with a prenatal diagnosis of DS who chose to continue with the pregnancy share the perspective that the utility of the test lies in allowing preparation for a child with special needs and being able to obtain resources and knowledge prior to the birth (Hurford et al 2013 ). It then becomes a question of balancing the benefit of preparation versus the anxiety it may bring (Michie 2020 ).…”
Section: Introductionmentioning
confidence: 99%